Numerical Analysis of the Magnetic Moment in S/F/S-Josephson Junction - Dieva, Elis (Computer Science and Interdisciplinary Research Journal, 2025)
One particularly intriguing object in superconductivity is the Josephson junction, which is an integral part of quantum computer hardware. Analysing this object requires solving differential equations. Such problems often cannot be solved with analytical methods; therefore, numerical methods and computational mathematics must be utilized. This article explores a fundamental model of the Josephson junction. The model presents the spatial coordinates of the magnetic moment as unknown functions dependent on time in a system of three ordinary differential equations with initial conditions. Comparative analysis of various methods is conducted for different sets of parameters. Optimal numerical methods for these particular instances of the problem are found. Visual results are also presented.